SRINAGAR: A MULTIFACETED GEM OF TOURISM - FROM NATURAL WONDERS TO HEARTWARMING HOSPITALITY - Shabir Ahmad Dar; Shahid Javid (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Tourism in the state has spurred the growth of the entire service industry, encompassing transportation, hospitality, camping, retail shops, horticulture, and small-scale sectors. However, this sector remains vulnerable to even minor fluctuations in the law and order situation. Srinagar, the summer capital of the Indian-administered union territory of Jammu and Kashmir, stands as an enchanting and prominent destination in the world of tourism. Nestled in the heart of the Kashmir Valley, this city's allure lies not only in its stunning natural beauty but also in its rich cultural heritage and warm hospitality, drawing travelers from across the globe. This descriptive exploration delves into the multifaceted role that Srinagar plays in tourism, taking readers on a journey through its picturesque landscapes, iconic houseboats on Dal Lake, Mughal Gardens, vibrant culture, diverse religious sites, and the exhilarating world of adventure tourism. Moreover, it unveils the heartwarming hospitality of the Kashmiri people, who extend genuine kindness and welcoming spirits to every visitor, creating not just a tourist destination but an unforgettable experience marked by both the city's natural wonders and the warmth of its inhabitants